Analysis of Employment Relationship with Nurse Performance at Special Eye Hospital, North Sumatra Province - Risda Risda; Mappeaty Nyorong; Juliandi Harahap (Journal La Medihealtico, 2022)
In the Special Eye Hospital of North Sumatra, it is known that there are several problems that occur which reflect the high number of nurses who experience work stress. This study aims to analyze whether there is a relationship between work stress and the performance of nurses in the Environment Eye Hospital Province Of North Sumatra This research was a quantitative research with a cross sectional research design. The study was conducted at the Environment Eye Hospital Province Of North Sumatra from July to August 2022. The number of samples was 43 nurses who were obtained by total sampling. The data in this study include primary data, secondary data and tertiary data. Data analysis was performed using univariate analysis test, bivariate analysis using Chi-square test and multivariate using logistic regression test. The results showed that in the univariate analysis of 43 respondents, most of the respondents aged > 35 years, as many as 24 (55.4%) respondents, female, as many as 40 (93.2%) respondents with D3 Nursing education as many as 34 (79 ,1%). In the bivariate analysis, it is known that there is a relationship between task demands (p value = 0.024), role demands (p value = 0.001), organizational structure (p value = 0.033), organizational leadership (p value = 0.024) with the performance of nurses in the Special Hospital Environment. Eyes of North Sumatra Province. The results of the multivariate analysis showed that the most dominantly related variable was the role demands variable (p value = 0.001).